The Influence of Classroom Interior Design on Early Childhood Learning Interests In Al-Hijrah Kindergarten Mandailing Natal Regency - Musdalifah Fifah; Armanila; Raudah Pertama Sari; Fennika Batubara (Tajdid Al-Athfal, 2022)
Interest adds excitement to every activity a person engages in. When students feel curious an habit, memories that will be very beautiful enjoyable when they are not happy. Interest in learning is something that arises from within that can be developed and fostered. The end of this observation is find out is answers about things problem formulation the Effect of Class Interior Design on Early Childhood Learning Interests in Al-Hijrah Kindergarten, Mandailing Natal Regency. This study uses a comparative descriptive research method with a population of 15 students and a sample of TK A and TK B classes. Using observation and documentation research instruments. Class interior design at Al-Hijrah Kindergarten, Mandailing Natal Regency has made a positive contribution in achieving curriculum targets by increasing students' interest in learning in carrying out the teaching and learning process